Emotional overload in forensic work: A narrative review of the literature - Santiago, Marizângela Lissandra de Oliveira; Macena, Raimunda Hermelinda Maia; Filho , Renato Evando Moreira; Cavalcante, Marcelo Borges; Mota, Rosa Maria Salani (Seven Editora, 2023)
The work of the scientific police in the investigation of violent crimes can cause an emotional overload of those professionals due to routine exposure to traumatic situations suffered by third parties, in addition to other stressors present in forensic work. Thus, the study aimed to investigate the factors inherent to forensic work capable of generating emotional overload in forensic professionals. It deals with a narrative review of the publications contained in the databases PubMed, Latin American and Caribbean Literature in Health Sciences (LILACS), and Scientific Electronic Library Online (SciELO). The results indicate that the manipulation of cadavers in several stages; the examination of the body of crime in victims of violence and the contact with family members in suffering; acting in grotesque scenes of homicides, suicides, and accidents; exposure to details of crimes in investigations from traumatic audiovisual material; and the responsibility for the expert report are aspects of the expert work that potentially trigger psychic alterations due to the emotional overload required to perform these activities. It is concluded that forensic police officers are vulnerable to the development of mental disorders due to the type of work activity performed, and there is a need to adopt preventive measures and health promotion for this population from institutional support. DOI:https://doi.org/10.56238/alookdevelopv1-090